Sepse, Sepse grave e choque séptico: aspectos clínicos, epidemiológicos, microbiológicos e prognóstico de pacientes de uma Unidade de Terapia Intensiva de um Hospital Universitário Brasileiro - Carvalho, Renan Henriques de (2008)
The study aim was to determine the incidence and evolution of sepsis, severe sepsis and septic shock, from hospitalar and community sample, if it was primary or secondary according to its origin and with or without microbiological identification. Furthermore it was assessed the etiology, the antibiotic susceptibility and their relationship with the antibiotic consume by patients of a mix adult Intensive Care Unit (ICU). It was realized an prospective observational study through active watchfullness at Hospital de Clínicas of Universidade Federal de Uberlândia (HC-UFU), for a nine months period (from april to december 2007). The total of 75 from 403 patients (18,6%, 15,9/1000 patient day) had sepsis, being 72% acquired inside the hospital and 28% from the community. The patient/day rate was 442, with patient/day rate for 1000 days of sepsis, severe sepsis and septic shock with respetive rate of 8,2; 5,0 and 3,1. The sepsis patient confinement time was 22,0 days. The sepsis patient mortality rate was ~ 35%, being higher in that patients with septic shock (50%). The microbiological identification presence was evident in 58% of the cases, with primary or secondary sepsis frequencies of 50,8% and 49,2% respectively, with the lung being the main place in the last group. The antibiotic usage rate was higher (60,3%) when compared to another studies. The sepsis risk factors were: confinement time higher than 5 days, parenteral nutrition, use of Central Vascular Catheter higher than 5 days and antibiotic usage. The main recovered pathoogens were those from Enterobacteriaceae family and Staphylococcus coagulase-negative, being observed the high proportion of antibiotic resistant phenotype. The nasal colonization by the S.aureus was expressive, appearing in almost 53% of the patients, being the most part (~ 61%) acquired outside the ICU, despite its frequencies as a sepsis agent was low (8%).